2021
DOI: 10.3389/fimmu.2021.656846
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Senescence Marker TIGIT Identifies Polyfunctional Donor-Reactive CD4+ T Cells Preferentially Lost After Kidney Transplantation

Abstract: Development of T-cell hyporesponsiveness to donor antigen may explain the substantial decreased risk for acute rejection in the years following kidney transplantation. The underlying mechanisms of donor-specific hyporesponsiveness (DSH) are largely unknown but may allow for lowering of immunosuppressive medication. Due to the onset of DSH being more rapid and pronounced in older recipients (+55 years), we hypothesized that immunosenescence/exhaustion of T lymphocytes would be a contributing factor. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
3
13
1
Order By: Relevance
“…43,44 Conversely, reduction in TIGIT-expressing polyfunctional CD41 T cells after kidney transplant enhanced tolerance and improved graft survival. 34 Our observation showing increased TIGIT expression after ischemic injury further implicates TIGIT in human AKI pathogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…43,44 Conversely, reduction in TIGIT-expressing polyfunctional CD41 T cells after kidney transplant enhanced tolerance and improved graft survival. 34 Our observation showing increased TIGIT expression after ischemic injury further implicates TIGIT in human AKI pathogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…A phenomenon known as donor-specific hyporesponsiveness (DSH) has been described in some kidney transplant recipients and is associated with a good long-term prognosis. A study described the novel finding that TIGIT-expressing donor-reactive CD4 + T cells decreased several years after kidney transplantation, which could explain the development of DSH [ 37 ]. We investigated the populations of CD226 + Tfh and TIGIT + Tfh cells and calculated the ratio of CD226 + Tfh cells to TIGIT + Tfh cells.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell studies can be valuable to identify biomarkers that could be predict rejection or tolerance following transplantation. 54,144,145 For example, Lau et al 54 identified via CyTOF a T-cell subset, distinct from classic T regulatory cells, that was associated with tolerance in pediatric liver transplant recipients. In addition, Pike et al 145 found that the pretransplant immune profile of the peripheral blood T cells was predictive for the risk of acute renal rejection in renal transplant recipients.…”
Section: Biomarker Identification and Risk Stratificationmentioning
confidence: 99%